Feasibility of the Manchester Acute Coronary Syndromes (MACS) decision rule to safely reduce unnecessary hospital admissions: a pilot randomised controlled trial. Issue 9 (12th May 2017) - Body, Richard; Boachie, Charles; McConnachie, Alex; Carley, Simon; Van Den Berg, Patricia; Lecky, Fiona E
Abstract : Background: Observational studies suggest that the Manchester Acute Coronary Syndromes (MACS) decision rule can effectively 'rule out' and 'rule in' acute coronary syndromes (ACS) following a single blood test. In a pilot randomised controlled trial, we aimed to determine whether a large trial is feasible. Methods: Patients presenting to two EDs with suspected cardiac chest pain were randomised to receive care guided by the MACS decision rule (intervention group) or standard care (controls). The primary efficacy outcome was a successful discharge from the ED, defined as a decision to discharge within 4 hours of arrival providing that the patient did not have a missed acute myocardial infarction (AMI) or develop a major adverse cardiac event (MACE: death, AMI or coronary revascularisation) within 30 days. Feasibility outcomes included recruitment and attrition rates. Results: In total, 138 patients were included between October 2013 and October 2014, of whom 131 (95%) were randomised (66 to intervention and 65 controls). Nine (7%) patients had prevalent AMI and six (5%) had incident MACE within 30 days. All 131 patients completed 30-day follow-up and were included in the final analysis with no missing data for the primary analyses. Compared with standard care, a significantly greater proportion of patients whose care was guided by the MACS rule were successfully discharged within 4 hours (26% vs 8%, adjusted OR 5.45, 95% CI 1.73 to 17.11, p=0.004). No patients in either group who were discharged within 4 hours had a diagnosis of AMI or incident MACE within 30 days (0.0%, 95% CI 0% to 20.0% in the intervention group). Conclusions: In this pilot trial, use of the MACS rule led to a significant increase in safe discharges from the ED but a larger, fully powered trial remains necessary. Our findings seem to support the feasibility of that trial. Trial registration number: ISRCTN 86818215. Research Ethics Committee reference: 13/NW/0081. UKCRN registration ID: 14334.